The prototype of smart Java editor: an initial approach of teaching and learning / Zamlina Abdullah … [et al.] - Abdullah, Zamlina; Othman, Zainab; Abu Bakar, Noor Suriana; Hasnan, Mazliana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Initially the use of recent Java programming language application has led to an extensive research on alternatives for better programming approach. This research is about Smart Java language editor. It is important that the current features of existing Java editor can be incorporated with some smart features of that will help students in learning Java programming. The smart mentioned here are smart tutoring systems, pop-up information, interactive and ease-of-language. Teaching strategy that is emphasized in this smart Java editor will prepare such interactive learning environment parable to the student's programming ability. Based upon the basic questions on Java programming language, students will be categorized into beginners or intermediates. Beginners need detail information to be presented, more helps and extra guidance. In comparison, intermediates need information and facts to be concisely and precisely presented. With this approach, it is hoped that the teaching and learning techniques of Java programming will be more effective.